Histone H3.3 lysine 9 and 27 control repressive chromatin at cryptic enhancers and bivalent promoters - Trovato, Matteo; Bunina, Daria; Yildiz, Umut; Fernandez-Novel Marx, Nadine; Uckelmann, Michael; Levina, Vita; Perez, Yekaterina; Janeva, Ana; Garcia, Benjamin A.; Davidovich, Chen; Zaugg, Judith B.; Noh, Kyung-Min (Nature Communications, 2024)
Histone modifications are associated with distinct transcriptional states, but it is unclear whether they instruct gene expression. To investigate this, we mutate histone H3.3 K9 and K27 residues in mouse embryonic stem cells (mESCs). Here, we find that H3.3K9 is essential for controlling specific distal intergenic regions and for proper H3K27me3 deposition at promoters. The H3.3K9A mutation resulted in decreased H3K9me3 at regions encompassing endogenous retroviruses and induced a gain of H3K27ac and nascent transcription. These changes in the chromatin environment unleash cryptic enhancers, resulting in the activation of distinctive transcriptional programs and culminating in protein expression normally restricted to specialized immune cell types. The H3.3K27A mutant disrupts the deposition and spreading of the repressive H3K27me3 mark, particularly impacting bivalent genes with higher basal levels of H3.3 at promoters. Therefore, H3.3K9 and K27 crucially orchestrate repressive chromatin states at cis-regulatory elements and bivalent promoters, respectively, and instruct proper transcription in mESCs.